Customers’ satisfaction and adaptations to service robots in a hotel environment - Vhugala Queen Kwinda; Nicola Wakelin-Theron (Tourism and Hospitality Management, 2025)
Purpose - The research aimed to investigate customers’ satisfaction and adaptations to service robots in various operational areas in a hotel. Although few hotels have introduced service robots in Africa, their creation is still in the initial stage and present challenges. The research objectives were to investigate customers’ satisfaction with service robots in a hotel and to determine customers’ adaptations to service robots in various hotel operational areas. Methodology - The study adopted an explanatory sequential mixed-method research approach. An online survey was used to collect quantitative data from hotel customers, while interviews were used to determine the customers’ adaptations and validate the quantitative results amongst hotel management. Findings - Customers are adapting well to service robots; however, they have mixed feelings about the presence of these robots in hotels. While they enjoy interacting with service robots in the hotel’s reception and additional services, amongst others, they still question the services that these robots provide. Originality - This study also contributes to the literature, managerial contributions, limitations, and recommendations for future research. Results from this research may help hotel managers to understand how the hospitality and tourism industries will have to adapt to customers’ satisfaction and adaptability towards robots in hotels.